2017
DOI: 10.1016/j.pmedr.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Population levels of, and inequalities in, active travel: A national, cross-sectional study of adults in Scotland

Abstract: This study aimed to describe active travel (walking or cycling) in Scotland and explore potential demographic, geographic, and socio-economic inequalities in active travel. We extracted data for the period 2012–13 (39,585 journey stages) from the Scottish Household Survey. Survey travel diaries recorded all journeys made on the previous day by sampled individuals aged 16 + living within Scotland, and the stages within each journey. Descriptive statistics were calculated for journey stages, mode, purpose and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
(32 reference statements)
3
16
2
2
Order By: Relevance
“…Our findings of divergent patterns in the recreational and active transportation domains in the US correspond with similar patterns found among adults using the same datasets as the present study [35]. Likewise, the higher levels of active travel for boys in low-income households in England agrees with findings of a greater likelihood of active travel among adults in more deprived areas in Scotland [36]. UK studies of younger children (7-8 year-olds) using accelerometry suggest no clear socioeconomic gradients in the time spent in MVPA [37]; however, activity monitors do not currently capture data on activity domain.…”
Section: Comparisons With Previous Studiessupporting
confidence: 88%
“…Our findings of divergent patterns in the recreational and active transportation domains in the US correspond with similar patterns found among adults using the same datasets as the present study [35]. Likewise, the higher levels of active travel for boys in low-income households in England agrees with findings of a greater likelihood of active travel among adults in more deprived areas in Scotland [36]. UK studies of younger children (7-8 year-olds) using accelerometry suggest no clear socioeconomic gradients in the time spent in MVPA [37]; however, activity monitors do not currently capture data on activity domain.…”
Section: Comparisons With Previous Studiessupporting
confidence: 88%
“…Prior studies have shown increased PA among lower SES populations, mostly due to PA associated with walking as participants are more likely to use active transportation for commuting. [48][49][50] Commuting does not explain our findings since there were no associations on working days, but our results emphasise the importance of focusing on non-working days when PA may take place in residential neighbourhoods. One prior study has assessed associations between neighbourhood characteristics and PA for different times of the day reporting stronger associations for times when adults were expected to be in their neighbourhood and awake (on weekdays before 9 am or after 5 pm and on weekends).…”
Section: Discussioncontrasting
confidence: 72%
“…That increased proximity to a new motorway was associated with increased likelihood of local active travel may suggest a health benefit, but may also reflect socioeconomic factors such as the aggregation of those without car access. A recent analysis of Scottish Household Survey 1 day travel diaries found likelihood of an active journey stage was higher for those living in the most deprived areas than for those in the least deprived [58]. The construction of a motorway, intended to facilitate motorised transport, in an area where nearly half the local population do not own a car (44% in our study participants), and therefore cannot make use of the infrastructure, may be contrary to the principles of social justice.…”
Section: Discussionmentioning
confidence: 99%